2017
DOI: 10.1016/j.eurpsy.2017.02.491
|View full text |Cite
|
Sign up to set email alerts
|

The structure of PTSD symptoms according to DSM-5 and IDC-11 proposal: A multi-sample analysis

Abstract: Posttraumatic stress disorder (PTSD) symptoms structure is a subject of ongoing debate since its inclusion in DSM-III classification in 1980. Different research on PTSD symptoms structure proved the better fit of four-factor and five-factor models comparing to the one proposed by DSM-IV. With the publication of DSM-5 classification, which introduced significant changes to PTSD diagnosis, the question arises about the adequacy of the proposed criteria to the real structure of disorder symptoms. Recent analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
(93 reference statements)
0
7
0
1
Order By: Relevance
“…M. Chen, Yoon, Harford, and Grant (2017) modeled a bifactor model using exploratory structural equation modeling in which a general distress factor accounted for most of the variance and orthogonal factors were distinguished on top of that. Several studies examined changes in prevalence rates based on different models of PTSD (e.g., Cyniak-Cieciura et al, 2017). All of this is in line with good external validation techniques (Elhai & Palmieri, 2011), and we encourage their continued application in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Chen, Yoon, Harford, and Grant (2017) modeled a bifactor model using exploratory structural equation modeling in which a general distress factor accounted for most of the variance and orthogonal factors were distinguished on top of that. Several studies examined changes in prevalence rates based on different models of PTSD (e.g., Cyniak-Cieciura et al, 2017). All of this is in line with good external validation techniques (Elhai & Palmieri, 2011), and we encourage their continued application in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…One article reported CFA results (Yang et al, 2017) that had been published in another as the first wave of a longitudinal invariance study (Wang et al, 2017); only the findings from the latter were used in the current review. One article reported results for two independent samples (Sachser et al, 2017) and another for four independent samples (Cyniak-Cieciura, Staniaszek, Popiel, Pragłowska, & Zawadzki, 2017). Our final sample was 23 publications, representing 27 independent samples.…”
Section: Methodsmentioning
confidence: 99%
“…The ES turned out to be insignificant only in the case of sensory sensitivity in prospective studies, groups exposed to occupational and combat trauma, in the studies using DSM -5 classification and FCB-TI(R) version. This result may be related either to changes in DSM definition of PTSD (as new symptoms of rather cognitive than emotional or somatic nature were added—the posttraumatic cognitions) or in FCB-TI version (as Sensory Sensitivity Scale content was significantly changed; see Cyniak-Cieciura et al, 2018; Cyniak-Cieciura et al, 2017). On the other hand, the result may also be related to the small number of studies using a prospective design, DSM -5 and FCB-TI(R) versions, and occupational and combat trauma populations, suggesting we need more studies of these types in order to be allowed to draw more specific conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that a seven-factor hybrid model that divided the current DSM-5 criteria into re-experiencing (B1–B5), avoidance (C1–C2), negative affect (D1–D4), anhedonia (D5–D7), externalizing behavior (E1–E2), anxious arousal (E3–E4) and dysphoric arousal (E5–E6) best described the underlying dimensionality of PTSD as defined in the DSM-5. 36 …”
Section: Present Of Ptsdmentioning
confidence: 99%